Kriteria Hukum Fikih Ja’fari - Abdul Rouf (Universitas Islam Negeri Jakarta, 2017)
The phenomenon of Shi'ism in the discourse of Islamic thought becomes one of the interesting as well as controversial discourse. Shia Ja‘farī, known as the Shi'a Imamiyah is often a priori addressed. A lot of the literature on the founder’s thinking contains prejudices. As a result,Shia Ja‘farī is not only underestimated, but also regarded as an aberrationor misdirection. Serious accusations are often leveled by Sunni against the Shias. This study poses the real issue, referring to some authoritative literature on Shia about the historical background of the birth of the Ja‘farī school, its criteria of law, its attitude to the Qur'an, the Hadith of the Prophet, reason and qiyas. DOI: 10.15408/ajis.v17i1.6221